Особливості розподілу легкоокиснюваних розчинених органічних речовин у воді різних ділянок водойм Києва - Осипенко, В.П. (Київський національний університет імені Тараса Шевченка, 2023)
Описані і обговорені результати вивчення загального вмісту і розподілу легкоокиснюваних розчинених органічних речовин у воді різних ділянок водойм Київа. Особлива увага приділена таким класам органічних сполук, як вуглеводи і білковоподібні речовини. У порівняльних таблицях представлені основні гідрохімічні характеристики води з різних досліджуваних ділянок, а саме: з чистоводдя і заростей вищих водяних рослин. Зокрема, визначені показники рН, вміст розчиненого у воді кисню, величини загального вмісту розчинених органічних речовин за параметрами хімічного споживання кисню (ХСК), концентрації вуглеводів і білковоподібних речовин. Також розраховані концентрації органічного вуглецю (Сорг.) і масові частки окремих досліджуваних органічних компонентів у загальному складі розчинених органічних речовин.

The results of study of the easily-oxidizable dissolved organic substances distribution in different Kyiv water bodies are described and discussed. Especially such classes of organic matters as carbohydrates and protein-like substances are investigated. In comparative tables the main hydrochemical characteristics on both the pure water part of lakes and the aquatic overgrowth part of lakes are presented. In particular the indexes of pH, dissolved oxygen concentration, the values of the total dissolved organic substances content according to parameters of chemical oxygen consumption (COC) by permanganat and bihromate oxidizability methods, carbohydrates and protein-like substances concentrations are difined. Also the concentrations of organic carbon (Corg.) and mass parts of different organic compounds in the total dissolved organic substances content are calculated. Among the water bodies studied by us, we observed a slight advantage of the total content of easily-oxidizable dissolved organic substances in overgrowth of higher aquatic plants (an average of 13,0 mg/dm3) over those in pure water (an average of 11,6 mg/dm3). But as all investigated urban water bodies are under significant anthropogenic load, not only natural organic substances but also pollutants could be in the water. The carbohydrates and protein-like substances concentrations, on the contrary, was lower in overgrowth areas of water bodies (an average of 3,10 and 0,58 mg/dm3 respectively). This fact, together with the low content of oxygen dissolved in water (an average of 4,9 mg/dm3), may indicate on the high degree of assimilation by aquatic plants of these organic components necessary for their growth and, as a result, on the ability of the water bodies to self-clean.
Features of distribution of the easily-oxidizable dissolved organic substances in water of different areas of Kyiv water bodies
Keywords: розчинені органічні речовини; вуглеводи; білковоподібні речовини; водойми Києва; dissolved organic substances; carbohydrates; proteins; water bodies of Kyiv